Islamic Religious Education in the Post-Human Era: Embracing Artificial Intelligence through Transformative Spirituality - Nasution, Suryadi; Pohan, Ali Jusri; Hayati, Nelmi; Khairurrijal, Khairurrijal; Nur, Kholidah (Graduate Program, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, 2025)
This research explores the implications of integrating artificial intelligence (AI) into Islamic Religious Education (PAI) in the post-human era, focusing on the transformation of spirituality and pedagogical approaches. Using a qualitative phenomenological approach, data were collected through in-depth interviews, participant observation, and digital content analysis involving 15 students, 10 PAI teachers, and 5 IT teachers from three Islamic high schools in North Sumatra. The findings indicate that AI enhances access to religious knowledge and stimulates critical reflection, but also creates emotional distance, spiritual narrative fragmentation, and theological oversimplification. Students experience religious hybridity, integrating technological logic with Islamic values, while teachers are polarized between adaptation and resistance. Ontologically, AI emerges as a new mediator in humanity's relationship with the transcendent, challenging the authenticity of spirituality. Pedagogically, AI offers the potential for modern relevance but demands curriculum revisions and teacher training. This study concludes that post-human PAI can enrich transformative spirituality through a synthesis of tradition and innovation, provided it is supported by contextually designed technology and theological collaboration, recommending a balanced learning approach for the future of PAI in the AI era